Relationship between curriculum and instructional materials of non-formal agricultural higher education - Musika, Araya; Poungsuk, Pakkapong; Siriwan, Nopakoon; Intorrathed, Sarawut (My University, 2019)
The research was to study the conditions of agricultural education of people and the relationship in the management model for non-formal agricultural education in Thailand. The data were collected via in-depth interviews structured with 56 respondents selected via purposive sampling. The results were most of respondents were female and the management model for agricultural education in curriculum and content, the most respondents showed the non-formal agricultural education without certain curriculum and course duration, including self-learning; teaching and learning showed the learning from the agriculture specialists and leaders in the community, obtained the knowledge from real practice; instructional materials showed the learning from real practice, friends' suggestions and conversations; assessment and evaluation showed the evaluation from work's outcome; The relationship of the curriculum and content with education and occupation, the instructional materials with education, the assessment and evaluation with education, the participation with education were statistically significance.
Keywords: Agricultural education; Higher education in Thailand; Management model of education; Model; Non-formal agricultural education